2010
DOI: 10.4037/ajcc2010180
|View full text |Cite
|
Sign up to set email alerts
|

Sound Intensity and Noise Evaluation in a Critical Care Unit

Abstract: Background Sound levels in intensive care units can be high. Unfortunately, high levels of sound tend to result in poor sleep quality, which leads to slower healing, poorer immune response, and decreased cognitive function. Objectives To measure sound levels to which patients in intensive care units are typically exposed. Methods Peak sound pressure levels of alarms on medical devices set at different output levels were measured. Additionally, ambient sound pressure levels for durations of 10 to 24 hours were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
65
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 35 publications
7
65
0
10
Order By: Relevance
“…3 In another study it was reported that daily noise level changed 41 dBA and 61 dBA at hospital environment. 8 In the study Khademi et al was reported daily noise level was reached 94 dBA and mean daily noise intensity was 60.2 dBA.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…3 In another study it was reported that daily noise level changed 41 dBA and 61 dBA at hospital environment. 8 In the study Khademi et al was reported daily noise level was reached 94 dBA and mean daily noise intensity was 60.2 dBA.…”
Section: Discussionmentioning
confidence: 96%
“…12,13 In an other study conducted by Lawson et al, it was stated that 56% of the noise source was alarms resulting from the devices at the ICU. 3 In another study, medical devices were indicated as a source of noise, especially ventilation system, bedside infusion pumps and monitor were reported noise sources. 14 In our study, we found that major cause of the noise was monitor alarms, 36 of total 50 patients (72%) were uncomfortable due to noise of these devices and the noise intensity was measured as 101.7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations